Quantum Computing at a Glance - Golec, M.; Hatay, E.S.; Gill, S.S.; Mao, Y.; Buyya, R. (Elsevier, 2025)
Quantum computing’s current capacity to efficiently tackle complex problems exceeds that of traditional methods, as demonstrated by its use in optimization and artificial intelligence. This chapter explains the concept of quantum computing, along with its differences from traditional computing. It further provides an overview of the fundamental elements of quantum computing, such as qubits, superposition, entanglement, and decoherence. Moreover, it discusses broadly quantum algorithms, quantum gates, quantum key distribution, quantum software tools, and quantum computing applications. It aims to highlight quantum computing’s revolutionary potential for solving complex problems and revolutionizing several fields. © 2025 Elsevier B.V., All rights reserved.
Keywords: Quantum Computing; Quantum Computing Algorithms; Quantum Computing Applications; Quantum Fundamentals; Quantum Key Distribution; Quantum Software Tools